Tracing Identity from Teeth to Technology: Artificial Intelligence in Forensic Dental Identification - Rajshree Borah; Cornelius Patrick Labella; Sreya Ghosh; Sonia Trivedi; Jaskaran Singh; Sahil Sharma; Richa Mishra (Indian Journal of Forensic Medicine and Pathology, 2025)
Identi𿿿cation is a key aspect particularly in the cases involving decomposition, mutilation or in mass disasters. Teeth own resilience hence, serves as a reliable marker to serve as a remedy for the purpose of identi𿿿cation. The explorationof teeth with AI revolutionized conventional methods of identi𿿿cationwithcontemporary ones yielding automation and better accuracy. This review portrays the transformation of conventional/manual comparison procedures of dentition to AI driven architectures. Advantageous enabling of AI strengthens reproducibility, transparency and standardization. However, this review also showcases the challenges associated with teeth identi𿿿cation such as ethical concerns, diversitypopulation and legal acceptance. Eventually, the convergence of computational intelligence with dentistry serves as a transformative era of tracing identity through technology.